2023
DOI: 10.24996/ijs.2023.64.2.6
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Antifungal Medications and Plant Extracts Against Candida albicans Isolated from Vulvovaginitis Women

Abstract: Fungus Candida spp. causes vulvovaginal candidiasis (VVC) which is a fungal infection of the genital mucosa. This investigation was on the isolation of Candida albicans from cervical-vulvovaginal patients in Erbil hospitals, Kurdistan region, Iraq and its identification is done using phenotypic and molecular approaches. Then biofilm production was detected through phenotypic tests such as Congo red agar (CRA) and disclosure virulence genes, agglutinin-like sequence(ALS1) and hyphal wall protein (HWP1). The sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The result of the current study was consistent with the finding of Hasan and Yasein (2018) All the macroscopic and microscopic characteristics of C. albicans and production of blastoconidia and chlamydospores, were similar to the findings of Atshan and Al-Haddad (2014) and Abdulla and Ismael (2023).…”
Section: Molecular Identification Of C Albicanssupporting
confidence: 93%
See 1 more Smart Citation
“…The result of the current study was consistent with the finding of Hasan and Yasein (2018) All the macroscopic and microscopic characteristics of C. albicans and production of blastoconidia and chlamydospores, were similar to the findings of Atshan and Al-Haddad (2014) and Abdulla and Ismael (2023).…”
Section: Molecular Identification Of C Albicanssupporting
confidence: 93%
“…The number of specimens under analysis and the numerous C. albicans isolation origins are factors that may contribute to the variability in the prevalence percentages of virulence genes as mentioned by (Vijayalakshmi et al, 2016). Abdulla and Ismael (2023) found that HWP1 genes were found in all C. albicans isolated.…”
Section: Molecular Identification Of C Albicansmentioning
confidence: 99%